A review of neuro-ophthalmic sequelae following COVID-19 infection and vaccination - Shi, Jane; Danesh-Meyer, Helen V. (Frontiers in Cellular and Infection Microbiology, 2024)
Background It has become increasingly clear that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can affect most organs in the human body, including the neurologic and ophthalmic systems. Vaccination campaigns have been developed at rapid pace around the world to protect the population from the fast-mutating virus. This review seeks to summarise current knowledge of the neuro-ophthalmic manifestations of both COVID-19 infection and vaccination. Evidence acquisition Electronic searches for published literature were conducted using EMBASE and MEDLINE on the 30th of July 2023. The search strategy comprised of controlled vocabulary and free-text synonyms for the following terms in various combinations: “coronavirus, COVID-19, SARS-CoV-2, 2019-nCoV, vaccination, vaccine, immunisation and neuro-ophthalmology”. No time range limits were set for the literature search. Published English abstracts for articles written in a different language were screened if available. Results A total of 54 case reports and case series were selected for use in the final report. 34 articles documenting neuro-ophthalmic manifestations following COVID-19 infection and 20 articles with neuro-ophthalmic complications following COVID-19 vaccination were included, comprising of 79 patients in total. The most commonly occurring condition was optic neuritis, with 25 cases following COVID-19 infection and 27 cases following vaccination against COVID-19. Conclusions The various COVID-19 vaccines that are currently available are part of the global effort to protect the most vulnerable of the human population. The incidence of neuro-ophthalmic consequences following infection with COVID-19 is hundred-folds higher and associated with more harrowing systemic effects than vaccination against the virus.